Locus of Control, Addiction Severity and Motivation to Change in Persons with Alcohol Use Disorder-A Cross-Sectional Study - Dr Deepak Kumar Rout; Jyotirmayee Pradhan; Dr Debasish Biswal; Dr. Jasobanta Mahapatra (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Alcohol use disorder becoming more prevalent claiming many adolescent, adult lives now a days with prolonged effects of cognitive disability and socio occupational impairment. Many patients presented to hospital during complication stage or withdrawal stage showing high motivation for abstinence again relapsed back with same condition as their locus of control was poor. This study aims to examine the locus of control and its correlation with motivation, readiness to change & severity of disease which was a significant predictor of relapse among those alcohol dependence patients. Aim: To assess severity of alcoholism, locus of control and the stages of motivation in patients with alcohol use disorder. To correlate locus of control and stages of readiness to change with severity of alcoholism. Material & Methodology:This is a cross sectional, observational study conducted in a tertiary care hospital of Cuttack, Odisha after obtaining ethical approval from 2020-21 with a sample size of eighty and participants assessed by locus of control, AUDIT & readiness to change questionnaire after obtaining informed consent. Diagnosis of alcohol dependence done on the basis of ICD 10 DCR criteria. Data compiled and statistical analysis on basis of categorical or continuous variables done. Pearson’s correlation test is used for assessing relationship between two groups. P < 0.05 was considered statistically significant. Results: Mean age of study participants is 32±4.6 yrs. The majority participants (70%) expressed having an external locus of control; hence, they attribute external factors to their alcohol use behavior. In terms of pattern of drinking habit 72% were showing dependence and rest are in harmful use pattern. There was a significant correlation of external locus of control with dependence pattern of alcohol use with [r = 0.675, p < 0.01]. A positive correlation r = 0.456, p < 0.05 was found between internal locus of control and action stage of readiness to change. Also, positive correlation, r = 0.446, p < 0.05 was found between dependence and contemplation stage. This indicates that addiction severity has a relationship with the contemplation stage of readiness to change. Conclusion: Major factors responsible for relapse among alcohol dependence in view of not able to maintain abstinence are external locus of control, stages of motivation and severity level of addiction. Those with high internal locus of control are professionally managed themselves in abstinence stage but those with high external locus of control are highly vulnerable to start addiction again. So more frequent follow ups and anticraving drugs will help them to maintain abstinence.